One Health: Wildlife, livestock and human health in the Mara-Serengeti ecosystem - International Livestock Research Institute (International Livestock Research Institute, 2020)
Land use policies can at times result in unintended consequences, often at the expense of entire ecosystems. This video on the privatization of land in and around the Mara-Serengeti in Kenya and Tanzania demonstrates how disease can spread when wildlife, livestock and humans cross over into each other's spaces. An integrated One Health approach in the management of landscapes can help mitigate or prevent disruption of these inter-related environments.